Role of the Hof1–Cyk3 interaction in cleavage-furrow ingression and primary-septum formation during yeast cytokinesis - Wang, Meng (Mol Biol Cell, 2018)
In Saccharomyces cerevisiae, it is well established that Hof1, Cyk3, and Inn1 contribute to septum formation and cytokinesis. Because hof1∆ and cyk3∆ single mutants have relatively mild defects but hof1∆ cyk3∆ double mutants are nearly dead, it has been hypothesized that these proteins contribute to parallel pathways. However, there is also evidence that they interact physically. In this study, we examined this interaction and its functional significance in detail. Our data indicate that the interaction 1) is mediated by a direct binding of the Hof1 SH3 domain to a proline-rich motif in Cyk3; 2) occurs specifically at the time of cytokinesis but is independent of the (hyper)phosphorylation of both proteins that occurs at about the same time; 3) is dispensable for the normal localization of both proteins; 4) is essential for normal primary-septum formation and a normal rate of cleavage-furrow ingression; and 5) becomes critical for growth when either Inn1 or the type II myosin Myo1 (a key component of the contractile actomyosin ring) is absent. The similarity in phenotype between cyk3∆ mutants and mutants specifically lacking the Hof1–Cyk3 interaction suggests that the interaction is particularly important for Cyk3 function, but it may be important for Hof1 function as well.